Microstructure Evolution and Multiscale Heat Transfer Characteristics of Resin-Based Ablative Material under Aerodynamic Heating - Junjie Gao; Daiying Deng; Haitao Han; Jijun Yu (International Journal of Aerospace Engineering)
This paper is aimed at investigating the microstructure evolution of resin-based ablative materials under aerodynamic heating. The microstructure, morphology, material density, and thermophysical parameters at different positions of the material after aerodynamic heating were deeply studied. The changes in the microstructural characteristics of materials caused by complex reaction processes were investigated, including microstructural morphology, porosity, the overlap relationship between microstructural components, and the mutual positional relationship. The relationship between microstructural evolution and material heat transfer is discussed. By analyzing the heat transfer mechanism and heat transfer path of the microstructure, combing with the analysis results of the evolution of the microstructure and the physical properties of the material, multiscale heat transfer unit cell models were established to predict the equivalent thermal conductivity. Thereby, the evolution of physical properties and microstructure of resin-based ablative materials under aerodynamic heating and the relationship between microstructure evolution and heat transfer process are obtained. It can improve the accuracy of ablative heat transfer simulation. In addition, it can provide reference for the process design of ablative materials and promote the application and development of ablative materials in the field of aircraft.